Hermeneutics in Contemporary Turkey: An Analysis of Turkish Historicists - Bacik, Gokhan (Religions, 2021)
The hermeneutical turn in Islamic studies has also affected Islamic scholarship in Turkey, a country where traditional Sunnism historically dominates. Historicism in Islamic studies became an influential intellectual and academic current in Turkey after the 1990s. This was mostly because the first generation of Turkish scholars, who associated themselves with historicism through complex engagement with Quranic hermeneutics in their studies, emerged in the 1990s. In this article, I analyze Mustafa Öztürk, İlhami Güler, and Ömer Özsoy, the architects of the historicist turn of the 1990s in Turkey who are still prominent. The article explains: (i) The Turkish historicists’ views on the nature of the Quran; (ii) Their hermeneutical approach in interpreting the Quran; and (iii) Illustrates how they apply the hermeneutical approach to the interpretation of the Quran by presenting how they interpret the Quran’s relevant verses on corporal punishment/chopping and divorce. The article aims to detail historicism in Turkey by studying its leading scholars.